From rejection to the Nobel Prize: Karikó and Weissman’s pioneering work on mRNA vaccines, and the need for diversity and inclusion in translational immunology - Bansal, Amit (Frontiers in Immunology, 2023)
Katalin Karikó and Drew Weissman were given the 2023 Nobel Prize in Physiology or Medicine for their findings of nucleoside base modifications that lead to the development of effective mRNA vaccines against COVID-19. This was a remarkable achievement, given that their initial manuscript was rejected by Nature and Science in 2005. The development of mRNA vaccines lagged for more than a decade for several reasons, including the lack of funding, the perceived risks of the technology, and the scepticism of many scientists. Furthermore, Karikó and Weissman's study appeared to be technical and difficult to understand. The COVID-19 pandemic, on the other hand, has shown the importance of mRNA vaccine technology. COVID-19 mRNA vaccines have been highly effective in preventing serious illness, hospitalization, and death. The Nobel Prize for Karikó and Weissman highlights the importance of perseverance, diversity, and inclusion in translational immunology. We need to build a more inclusive scientific community, where scientists from all backgrounds are supported and their work is valued. This will result in more scientific breakthroughs and better healthcare for everyone.